Protestantski silabizem - Bjelčevič, Aleksander (Jezik in slovstvo, 2000)
In a song syllabism means that word stress and beat frequently do not coincide. Syllabicity can be measured with a simple count: we need to establish how many stressed syllabels are there in individual syllabic position in a line. Errors due to incorrect stress assignment can be neutralised with comparative analyses of: a) protestant songs and more rythmic Catholic songs from the 16th century; b) protestant verse and prose. The results show that the protestant verse is less rythmic than the Catholic one, but rythmically the same as protestant verse.
Keywords: Slovene literature; slovenska književnost; slovenska poezija; cerkvena poezija; posvetna poezija; verz; silabizem; 18.st.